Impact of celebrity credibility on advertising effectiveness - Sadia Aziz; Usman Ghani; Abdullah Niazi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Advertisers often make use of endorsers or representatives as trustworthy sources of persuasion for consumers' attitudes. Promotion of products through celebrities is a trendy advertising practice around the world. The present study judged the impact of celebrity credibility on advertising effectiveness in terms of consumer's attitude towards the advertisement, attitude towards the brand and their purchase intention. This study also explored the differences of respondent's responses towards the advertisements of brand through famous celebrities as well as unknown celebrities. Different TV advertisements were used for the experiment. Several statistical tools were applied to test the hypotheses and identify significant differences & the proposed relationships among the variables. Overall findings suggests that the respondents considered the famous celebrities of the brand as the most credible celebrities, having positive impact on consumers attitude towards the advertisement, attitude to the brand and their favorable purchase intentions as compare to the unknown celebrity with less credibility.
Keywords: 330; Celebrity credibility; advertisement; attitude toward advertisement; attitude toward brand; purchase intention